Gastro-oesophageal reflux disease in 'difficult-to-control' asthma: prevalence and response to treatment with acid suppressive therapy - Wong, C.H.; Chua, C.J.; Liam, C.K.; Goh, Khean Lee (Blackwell Publishing, 2006)
BACKGROUND: The causal association between gastro-oesophageal reflux disease (GERD) and difficult-to-control asthma is unclear.